Nucleot(s)ide Analogs for Chronic Hepatitis Virus Therapy: A Global Bibliometric Analysis (1986-2022) (Bangladesh Journal of Medical Science, 2024)
Objectives: This  study  aimed  to  analyze  the  global  profile  of  the nucleotide/nucleoside  analogs  (NAs)  for  chronic  hepatitis virus therapy-related research.Background: NAs, which closely resemble the structure of naturally occurring  nucleotides/nucleosides,  function  by  disrupting the elongation of the nascent DNA strand. These compounds are  considered  safe  and  well-tolerated,  as  they  specifically target  viral,  but  not  human,  polymerases  involved  in  DNA replication.  NAs  are  crucial  in  treating  viral  infections, including hepatitis, and are widely used due to their efficacy and safety. However, a study about trends in NAs for chronic hepatitis therapy-related research was never reported before.Methods: The  NAs  for  chronic  hepatitis  therapy-related  research bibliometric  analysis  was  performed  on  articles  indexed  in the Scopus database from 1986 to 2022.Results: The  total  number  of  articles  published  worldwide  is  2,341 documents,  with  an  annual  average  of  65  documents.  The United States generated the most articles (n = 486), followed by China (n = 454), France (n = 191), and Italy (n = 179). Since 1992, the number of publications has increased dramatically worldwide. Globally, liver cell carcinoma, antiviral therapy, hepatitis  B  (e)  antigen,  and  alanine  aminotransferase  are becoming hot research topics in the field.Conclusions: This  study  provides  a  unique  composite  picture  of  NAs for  chronic  hepatitis  therapy-related  research  worldwide and  evaluates  research  productivity  from  1986  to  2022. This finding suggests that the prospects for interventions in chronic hepatitis remain promising.Bangladesh Journal of Medical Science Vol. 23 No. 03 July’24 Page : 747-756